2013
DOI: 10.7314/apjcp.2013.14.12.7351
|View full text |Cite
|
Sign up to set email alerts
|

Renal Cell Carcinoma is More Aggressive in Turkish Patients with the Metabolic Syndrome

Abstract: Background: Metabolic syndrome (MetS) is a multifactorial disease characterized by impaired glucose tolerance/diabetes, obesity, high triglyceride levels, low HDL levels, and hypertension. In this study we evaluate the relationship between tumor size and grade, and presence of the metabolic syndrome in patients with renal cell carcinoma. Materials and Methods: Between 2007-2013, radical nephrectomy was performed for 310 patients with renal tumors in our clinic and those with pathology reported renal cell carci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
19
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 33 publications
0
19
1
Order By: Relevance
“…The MetS (Ozbek et al, 2013) and diabetes mellitus itself have been shown to be associated with aggressive RCC in terms of higher tumor size and nuclear (Fuhrman) grade in recent studies that performed also in Turkish population. Their results point out a possible association between MetS and tumor carsinogenesis, eventhough we did not confirm any link either between MetS and nuclear grade or between MetS and RCC subtype.…”
Section: Discussionmentioning
confidence: 96%
“…The MetS (Ozbek et al, 2013) and diabetes mellitus itself have been shown to be associated with aggressive RCC in terms of higher tumor size and nuclear (Fuhrman) grade in recent studies that performed also in Turkish population. Their results point out a possible association between MetS and tumor carsinogenesis, eventhough we did not confirm any link either between MetS and nuclear grade or between MetS and RCC subtype.…”
Section: Discussionmentioning
confidence: 96%
“…Patients with RCCs are usually older, with the mean age at diagnosis of 60 years (Ozbek et al, 2013). The highest incidence of this disease is found in North America and Europe.…”
Section: Discussionmentioning
confidence: 99%
“…Higher grade is associated with the biological aggressiveness and increased metastatic potential of the tumour. Most of the RCCs are classified as grade II in the studies (Pichler et al, 2012;Ozbek et al, 2013). The proportion of grade II tumours was between 43 and 61.5%.…”
Section: Discussionmentioning
confidence: 99%
“…Notably, cancer is the leading cause of death and is associated with the largest disease burden in Korea Jung et al, 2014). Many studies have suggested that obesity is related to all-cause mortality and cancer mortality (Calle et al, 2013;Flegal et al, 2013;Ozbek et al, 2013). Indeed, the risk of death from cancer increases with body mass index (BMI) (Jee et al, 2006;.…”
Section: Introductionmentioning
confidence: 99%